Exploring the Shared Meaning of Social Inclusion to Children with and without Disabilities. (3rd September 2021) - Edwards, Brydne; Cameron, Debra; King, Gillian; McPherson, Amy C.
Abstract: Aims: Perspectives of children with and without disabilities on social inclusion are seldom sought in the childhood disability literature, impeding the ability to provide inclusive experiences for all children. This qualitative study explored meaningful aspects of social inclusion from the perspectives of children with and without disabilities in an inclusive recreation program. Methods: Drawing on the interpretive paradigm and subjectivity epistemology, this study adopted a generic qualitative methodological approach. Seventeen children with and without disabilities involved in the same inclusive recreation program participated in two semi-structured interviews. These interviews were analyzed using an inductive thematic analysis. Results: Three key themes emerged and were interpreted as dimensions of social inclusion: contextual, intrapersonal, and interpersonal. The contextual dimension included the freedom to choose activities and receiving equal attention from staff. The intrapersonal dimension was characterized by psychological safety and group fellowship. The interpersonal dimension included having positive authentic interactions and giving/receiving help. Conclusions: These findings may influence future program development and implementation to promote inclusive experiences for all children.